2022
DOI: 10.1093/tropej/fmac065
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Infant Deaths in Indonesia: An Analysis of the 2012 and 2017 Indonesia Demographic and Health Surveys

Abstract: Background This exploratory study aimed to investigate factors related to infant deaths using a conceptual framework that explains the risk factors of infant deaths in developing countries. Methods The study adopted a cross-sectional study design and used data from the 2012 and 2017 Indonesia Demographic and Health Surveys, with a sample of 3694 singleton live births in 2012 and 3413 in 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…Similarly, infants born with a small birth size had a higher risk of infant mortality than infants born with a large birth size. This result is in line with the previous findings in Ethiopia 19 , 20 , Bangladesh 14 , 42 and Indonesia 43 . Poor nutritional status may have an impact on size at birth, which may have an impact on the risk of newborn mortality 19 .…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, infants born with a small birth size had a higher risk of infant mortality than infants born with a large birth size. This result is in line with the previous findings in Ethiopia 19 , 20 , Bangladesh 14 , 42 and Indonesia 43 . Poor nutritional status may have an impact on size at birth, which may have an impact on the risk of newborn mortality 19 .…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note, however, that the reported prevalence rates varied significantly even among the studies that used relatively similar approaches and were conducted in comparable settings [69,70]. This was also observed among the studies that reported following the WHO's recommendation [14,17,[36][37][38][39][40][41][42][43][44], indicating that not only the methodological differences but also other contextual factors might have also contributed to the observed variation.…”
Section: Discussionmentioning
confidence: 91%
“…Further, 53 studies were specific to short birth interval and reported on either the prevalence or the predictors and 87 studies were not specific to short birth interval but considered birth interval as a covariate (Table S6 in the Online Supplementary Document). Characteristics of the studies that followed the WHO recommendation [14,17,[36][37][38][39][40][41][42][43][44] for the definition and classification of short birth interval are presented in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…First, the IDHS is nationally representative and has a high response rate (97-99%) [ 16 ]. Second, a standardized questionnaire was used, which has been validated by many previous research studies [ 16 ]. However, there are also some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Significance was determined using a p-value <0.05 and 95% confidence intervals (CIs). Potential components for the multivariate analysis were included based on bivariate analysis with a p-value <0.2 [ 16 ]. The first step involved incorporating household characteristics in the multivariate analyses, followed by the addition of parental characteristics to the final model.…”
Section: Methodsmentioning
confidence: 99%